Problems and ways of perfection of physical training of junior officers - A.V. Maglovanyy; A.M. Boyarchuk (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Research of level and dynamics of physical preparedness of cadets of military institute during all period of education and young officers during the first three years of service in officer positions was conducted. The cadets of 1-5 courses (n=158) and officers of 1 age group (n=42) took part in researches. The level of physical preparedness was determined as a result of running on 100 m, pulling up on a cross-beam, running on 3000 m. It is set, that the results of cadets grow to the 4 course and stabilize and even gone down on 5 course. The level of physical preparedness of young officers, who had a desire to systematic employments by physical exercises during period of education in the institute, remains high during 3 years after the finishing. At young officers who are not independently engaged in physical preparation, the level of development of physical qualities gets worse in the process of service.